Clinical characteristics and treatment patterns of patients with episodic cluster headache: results from the United States, United Kingdom and Germany - Cotton, Sarah; Andrews, Jeffrey S; Nichols, Russell M; Jackson, James; Tockhorn-Heidenreich, Antje; Milligan, Gary; Martinez, James M (Current medical research and opinion, 2023)
To describe clinical characteristics and regional treatment patterns of episodic cluster headache (CH). A point-in-time survey of physicians and their patients with CH was conducted in the United States, United Kingdom and Germany in 2017. Overall, 1012 patients with episodic CH were analyzed. Demographic and clinical findings were generally consistent across regions. Most patients were men (66.6%) and the mean age was 40.9 years. The greatest proportion of patients (38.3%) had ≤1 attack per day. The mean number of attacks per day (APD) was 2.4 and mean number of cluster periods per year was 2.6; the mean cluster period duration was 30.8 days. Most patients (69.3%) did not report a specific or predicable time when cluster periods occurred. Acute treatment was prescribed for 47.6% of patients, 10.3% of patients received preventive treatment, and 37.9% of patients received combined acute and preventive treatment; 4.2% of patients were not receiving treatment. Frequently prescribed acute treatments were sumatriptan, oxygen, and zolmitriptan; oxygen use varied considerably across countries and was prescribed least often in the United States. Frequently prescribed preventive treatments were verapamil, topiramate, and lithium. Lack of efficacy and tolerability were the most common reasons for discontinuing preventive treatment. We observed high use of acute treatments, but only half of patients used preventive treatments despite experiencing several cluster periods per year with multiple cluster APD. Further studies about the need for and benefits of preventive treatment for episodic CH are warranted.